Beneficial Immune Regulation by Biological Response Modifier Glucans in COVID-19 and Their Envisaged Potentials in the Management of Sepsis - Preethy, Senthilkumar; Raghavan, Kadalraja; Dedeepiya, Vidyasagar Devaprasad; Surya Prakash, Vaddi; Ikewaki, Nobunao; Ikeue, Yasunori; Nagataki, Mitsuru; Iwasaki, Masaru; Senthilkumar, Rajappa; Abraham, Samuel J. K. (Frontiers in Immunology, 2022)
Sepsis is a life-threatening condition caused by an abnormal immune response induced by infection with no approved or specific therapeutic options. We present our perspectives for the therapeutic management of sepsis through a four-way approach: (1) infection control through immune enhancement; (2) immune suppression during the initial hyper-inflammatory phase; (3) balanced immune-modulation to counter the later immune-paralysis phase; and (4) advantageous effects on metabolic and coagulation parameters throughout. COVID-19 is a virus-triggered, accelerated sepsis-like reaction that is associated with the rapid progress of an inflammatory cascade involving a cytokine storm and multiorgan failure. Here, we discuss the potential of the biological response modifiers, β-glucans (BRMGs), in the management of sepsis based on their beneficial effects on inflammatory-immune events in COVID-19 clinical studies. In COVID-19 patients, apart from metabolic regulation, BRMGs, derived from a black yeast, Aureobasidium pullulans strain AFO-202, have been reported to stimulate immune responses. BRMGs, produced by another strain (N-163) of A. pullulans, have been implicated in the beneficial regulation of inflammatory markers and immunity, namely IL-6, C-reactive protein (CRP), D-Dimer, ferritin, neutrophil-to-lymphocyte ratio (NLR), lymphocyte-to-C-reactive protein ratio (LCR), leucocyte-to-C-reactive protein ratio (LeCR), and leukocyte-to-IL-6 ratio (LeIR). Agents such as these β-glucans, which are safe as they have been widely consumed by humans for decades, have potential as adjuncts for the prevention and management of sepsis as they exert their beneficial effects across the spectrum of processes and factors involved in sepsis pathology, including, but not limited to, metabolism, infection, inflammation, immune modulation, immune enhancement, and gut microbiota.